APPLICATION OF ENAGRAVING MACHINE CONTROLLED BY COMPUTER IN TECHNICAL EDUCATION - TVARUZKA, Vaclav (Trends in education, 2013)
This paper deals with the lessons of programming and working with engraving machine in education of future teachers. It describes technical parameters and essential information that accompany teaching of operation and work (didactic order of the topic realization including). CNC machine enables activate students to deeper knowledge of mastering technological equipments. An important factor is a possibility to use this technology as a hobby, a modelling and a creation of decorative items..
Keywords: CNC machine; technology; activate students; procedural skils